Role of the Spinal Trkb-Nmda Receptor Link in the Bdnf-Induced Long-Lasting Mechanical Hyperalgesia in the Rat: A Behavioural Study - Hernandez-Kunstmann, A; Marcos-Camus, J; Constandil-Cordova, L (Blackwell Publishing Ltd, 2017)
Background: Intrathecal/intracisternal BDNF in rodents produces long-lasting hyperalgesia/allodynia, which implies BDNF plays a role in the establishment and maintenance of central sensitization. Both self-regeneration of endogenous BDNF and neuroplastic modifications of spinal NMDA receptors downstream TrkB signalling could be involved in such enduring hyperalgesia. We investigated to what extent BDNF by itself could participate in the generation and maintenance of mechanical hyperalgesia using pharmacological tools. Methods: We studied sensitivity of mechanical hyperalgesia induced by a single intrathecal (i.t.) injection of BDNF (3 ng/10 μL i.t.) administered at time zero, for: (1) chronic NMDA receptor inhibition with subcutaneously implanted 7-day delivery osmotic pumps loaded with ketamine; (2) TrkB receptor inhibition with intraperitoneal (i.p.) cyclotraxine-B; and (3) chronic glial inhibition with repeated propentofylline i.t. injections. Nociceptive threshold to paw pressure, tested on days -3, 0, 3, 7, 10 and 14, was used as the index of central sensitization. Locomotor patterns and food and water consumption were assessed with LABORAS. Results: Chronic ketamine prevented the mechanical hyperalgesia induced by BDNF, without affecting locomotion and food and water consumption. After pump depletion, a late hyperalgesic response to paw pressure stimulation emerged, which can be lastingly antagonized by cyclotraxine-B. Chronic propentofylline treatment irreversibly suppressed BDNF-induced hyperalgesia. Conclusion: Activation of NMDA receptors downstream to TrkB signalling is essential for behavioural expression of the mechanical hyperalgesia induced by intrathecal BDNF. However, maintenance of the hyperalgesia depends mainly from self-regenerating glial BDNF rather than from a NMDA receptor-dependent form of neuroplasticity. Significance: Intrathecal BDNF induces long-lasting central sensitization via a glial-likely BDNF self-regenerating mechanism, whose behavioural expression depends on downstream activation of NMDA receptors. This knowledge suggests that TrkB antagonists could represent an interesting lead for the development of novel therapeutic strategies for some chronic pain conditions.